Implementation Of Naive Bayes Method In Classification Of Prospective Kartu Keluarga Sejahtera - Hendri Hendri; Rachman Komarudin; Dony Oscar; Agus Salim; Nurul Afni; Yana Iqbal Maulana (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Kartu Keluarga Sejahtera is an assistance for underprivileged families that aims to help the poor, which is expected to ease the burden on society. Sumberjaya Village is one of the villages that has a total population of 73,631 people. The provisions in determining the status of Kartu Keluarga Sejahtera recipient are based on observations and interviews with the Head of the Sumberjaya Village Planning Affairs regarding the process of receiving Kartu Keluarga Sejahtera which is still not optimal in the data collection process so that there is still data Inaccurate in its acceptance, therefore it is necessary to conduct an assessment using the Naive Bayes method to give a classification to the process of receiving Kartu Keluarga Sejahtera, namely by determining age, gender, marital status, education, occupation, income, number of dependents, type of building and owner status. House. It is hoped that the data generated from this process can be used as material for evaluating the process of receiving / not receiving Kartu Keluarga Sejahtera.